(untitled) (AYUSHDHARA, 2024)
Ayurveda stands as an ancient and profoundly beneficial discipline for humanity, rooted in the Tridosha, Saptdhatu, Panchmahabhuta theories. Among these Doshas, Vata holds a pivotal role in both states of well-being and illness. It encompasses five subdivisions, namely Prana, Udana, Samana, Vyana, and Apana. Samana Vayu, situated proximate to the Jatharagni or digestive fire, traverses the entirety of the gastrointestinal tract (GIT). Its function involves stimulating Agni for efficient digestion, facilitating the breakdown of nutrients, and aiding in the movement of gastrointestinal contents. Coordinated with Prana Vayu, it initiates the intake of food into the digestive system, while working with Apana Vayu to expel waste materials from the body. The functionalities of Samana Vayu closely mirror the physiological actions of structures within contemporary medical science. Specifically, it can be likened to the Enteric Nervous System (ENS) and Autonomic Nervous System (ANS) which regulates the gastrointestinal tract (GIT) through both sympathetic and parasympathetic pathways. Diets rich in proteins, lipids and fats are known to enhance the stimulation of Agni, the digestive fire, thereby promoting digestion and facilitating the movement of gastrointestinal products. This process can be likened to the concept of Samanvayu, which orchestrates the coordination and harmonious functioning of various physiological processes, including digestion, absorption, and other gastrointestinal functions.